Executive functions in young patients with unipolar depression - Totić-Poznanović Sanja; Marinković Dragan; Pavlović Dragan; Tomić Gordana; Paunović Vladimir R. (Srpski Arhiv za Celokupno Lekarstvo, 2006)
Neuropsychological deficits associated with unipolar depression are seen in a broad range of cognitive domains. Executive deficits may be prominent in depression. Investigation of executive functions in younger adult patients with unipolar depression has been the focus of our study. Twenty-two consecutively depressive inpatients (24-36 years) and 21 healthy control subjects, matched on age, gender, education and verbal IQ were included in the study. Neuropsychological tests for executive functions were applied to all subjects. Unipolar young depressives showed significantly reduced number of completed categories and more trials for completion of the first category on Wisconsin Card Sorting Test (WCST). No difference of tasks assessing the short-term memory, total errors on WCST, perseverative and non-perseverative errors, and of both phonemic and semantic conditions of verbal fluency was found between groups. The results suggested that unipolar depressives had specific cognitive style characterized by "negative cognitive set" (stronger negative reaction to negative feedback) and by failure to use negative feedback to improve their performance.